Nurses’ perceptions and attitudes towards family presence during resuscitation in adult critical care units - Chung Su Chin; Pauline Stitt (Malaysian Journal of Medicine and Health Sciences, 2020)
During resuscitation efforts, patients’ families are routinely barred from the resuscitation area. Even there is an increased in demand from the family members requesting to be present during resuscitation of their loved one, health care providers not always offer the option for family presence. The major concerns of health care providers who are opposed to family presence during resuscitation (FPDR) were fear of psychological trauma to family members who witnessed the resuscitation. This study aimed to examine the critical care nurses’ perception and attitudes towards the presence of patients’ family members during resuscitation in adult critical care units. Methods: Study papers included were narrowed to primary study, published within 2003-2014, describing nurses’ perceptions and attitudes on an adult inpatient family witnessed resuscitation in critical care units. Results: Seven studies included, and four main themes emerged mainly samples population, nurses’ experiences of FPDR, nurses’ responses toward FPDR and factor predicting nurses’ attitudes toward FPDR. 20% - 42.2% of nurses had experienced FPDR. Only 4% - 6% of study participants working in hospital with established policy and 95% - 100% had not invited family members to witnessed resuscitation. Nurses would consider the option if family members are accompanied by trained staff. Nurses concern included difficult to concentrate, negatively affecting their performance, increased rate of legal action, inadequate staff and limited space. Concerns on family members included too distressing event, negative psychological impact argue and interfere with staff. Concerns on patient would be breach of confidentiality. Conclusion: Adult critical care nurses demonstrated negative perceptions and attitudes towards FPDR. Study participants in this review are not familiar with the concept of FPDR. There is a need for policy development and education on FPDR.